Dielectric performances of palm oil and coconut oil-based nanofluids with surfactants - Mohamad, Nur Aqilah (2020)
With the current interest of green technology application in transformers, PO and CO have been introduced as viable alternatives for MO. Previous studies have shown that the dielectric performances of these oils are comparable with MO. These properties however could be further improved through introduction of conductive, semi-conductive and insulative nanoparticles. Currently, there are only few studies that have been conducted in this area for these oils, which prompt for in-depth investigation. In addition, the roles of ionic and non-ionic surfactants for vegetable based nanofluids are quite limited which warrants for further investigation for its feasibility to enhance the effectiveness of the nanoparticles. This study aims to examine the dielectric performances of RBDPO and CO in the presence of Fe3O4, CuO and Al2O3 nanoparticles with surfactant. The types of surfactants used in this study were CTAB, SDS and OA. Fourier transform infrared and particle size distribution were used to characterize the nanoparticles in the oils. MO was also examined for comparison purpose. The AC breakdown voltage was carried out and the data was analysed for the AC withstand voltage at 1% probability. The Al2O3 was chosen for the lightning breakdown voltages and PD since it could provide the highest improvement of AC breakdown voltage. The lightning breakdown test was carried out based on needle-sphere electrodes configuration at the gap distance of 25 mm under positive and negative polarities. The PD were measured based on needlesphere electrode configuration at the gap distance of 50 mm. Rising voltage method was applied for the lightning breakdown voltage and PDIV measurements. A photo multiplier tube was also used to detect faint optical signals from weakly emitting sources during the PD test. It is found that only Al2O3 can improve the average AC breakdown voltage of RBDPO and CO. The AC withstand voltages at 1% probability for RBDPO, CO and MO could be improved through introduction of Fe3O4, CuO and Al2O3 at certain volume concentrations. OA could provide the highest improvement of the AC withstand voltages at 1% probability for RBDPO, CO and MO based Al2O3 nanofluids. Al2O3 could improve both positive and negative lightning breakdown voltages of RBDPO and CO. Under both polarities, CTAB provide the highest improvements on the lightning breakdown voltages of RBDPO, CO and MO based Al2O3 nanofluids. CTAB further increases the times to breakdown and decrease the average streamer velocities of RBDPO based Al2O3 nanofluid under both polarities. The same finding is observed for CO under positive polarity with CTAB and SDS as well as under negative polarity with all surfactants. It is found that, RBDPO, CO and MO based Al2O3 nanofluids have second mode of streamer whereby the streamer velocities are from 1 km/s to 3.4 km/s regardless with or without surfactants. The presence of Al2O3 does improve the PDIV of RBDPO and CO without and with either CTAB or SDS. The maximum PD amplitudes of RBDPO, CO and MO could further be enhanced in the presence of Al2O3 with either SDS or OA. On the other hands, the PD repetition rates for RBDPO, CO and MO improve in the presence of Al2O3 regardless with and without surfactants. Al2O3 leads to the increment of light signal emissions for RBDPO and CO and it is further enhanced in the presence of surfactants.